Green Software Process Assessment: The Theoretical Framework (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many differentdomains such as engineering, education and health apply green development through sustainability concept.The aim is to ensure the product and services are still relevance and applicable for the next generation. Previously, they were three common pillars of sustainability elements which were economic, social, and environmental. The technical and individual elements were added later to evaluate the software system. Yet, effortsare made to achieve green development process by reducing wastes and to preserve the environment.Most studies targeted on greenness of software products and less consideration on green in software processes. In this study, focus is given to ensure and guarantee green in software process activities. This paper presents the background works on existing studies in green software process and related. Further, it presents the theoretical framework that is based on literature findings and will be the groundwork of this study. The theoretical frameworkdefined consists of software process, green context, and assessment method. The elements of sustainability and waste reduction will be identified further.